ANALYSIS OF Pb, Cr, Cu and Zn CONCENTRATIONS IN SHELLS OF BLOOD COCKLE’S (Anadara granosa) FROM SINGKEP ISLAND COASTAL WATERS, THE PROVINCE OF RIAU ARCHIPELAGO - Effino Panji Sudewo; Yusni Ikhwan Siregar; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted from January to February 2018 by taking samples of blood cockles from  the coast of Singkep Island, Lingga Regency, Riau Archipelago Province. The purpose of this research were to know the metal concentrations of Pb, Cr, Cu and Zn in different station and different sizes of blood cockle’s shells (Anadara granosa), as well as to find out the level of metal pollution based on MPI (Metal Pollution Index). Analysis of metal concentrations of heavy metal was done by following procedures outlined by Yap et al., (2003). The results showed that the highest metal concenration of Pb was found in medium-size (11.8200 µg/g) at Station 1. Highest concentration of Cr was found in small size (20.5453 µg/g) at Station 1, highest Cu found in small size (18.8987 µg/g) at Station 1, and the highest  Zn was found in large size (48.2413 µg/g) at Station 1. The calculated MPI value for coastal water of Singkep Island from this research was 14.66 which considered as quite high.Key Words: Heavy Metal, Pollution, Riau, Mining, Anadara granosa